PEMBELAJARANÃÂ KOMPETENSIÃÂ PEMELIHARAANÃÂ DANÃÂ PERBAIKANÃÂ SISTEMÃÂ BAHANÃÂ BAKARÃÂ MENGGUNAKANÃÂ MEDIAÃÂ MEJAÃÂ DANÃÂ WIRINGÃÂ DIAGRAM - TarjuniÃƒÂ‚Ã‚Â , -; AnisÃƒÂ‚Ã‚Â , Samsudin; BudiyonoÃƒÂ‚Ã‚Â , ArisÃƒÂ‚Ã‚Â (Jurnal Pendidikan Teknik Mesin, 2008)
TujuanÃÂ  penelitianÃÂ  iniÃÂ  adalahÃÂ  untukÃÂ  mengetahuiÃÂ  perbedaanÃÂ  kompetensiÃÂ  pemeliharaanÃÂ  danÃÂ  perbaikanÃÂ sistemÃÂ  bahanÃÂ  bakarÃÂ  mesinÃÂ  dieselÃÂ  padaÃÂ  siswaÃÂ  tingkatÃÂ  XIÃÂ  SMKÃÂ  IslamÃÂ  PemalangÃÂ  tahunÃÂ  diklatÃÂ  2008/2009ÃÂ  denganÃÂ menggunakanÃÂ  duaÃÂ mediaÃÂ  pembelajaranÃÂ  berbedaÃÂ  yaituÃÂ mediaÃÂ mejaÃÂ  danÃÂ wiringÃÂ  diagramÃÂ  sistemÃÂ  pemanasanÃÂ  awal.ÃÂ PopulasiÃÂ danÃÂ sampelÃÂ padaÃÂ penelitianÃÂ  iniÃÂ adalahÃÂ siswaÃÂ tingkatÃÂ XIÃÂ TMOÃÂ 1ÃÂ danÃÂ siswaÃÂ tingkatÃÂ XIÃÂ TMOÃÂ 2ÃÂ tahunÃÂ diklatÃÂ 2008/2009.ÃÂ DataÃÂ diambilÃÂ dariÃÂ  tesÃÂ  kemampuanÃÂ  awalÃÂ  siswaÃÂ untukÃÂ mengetahuiÃÂ bahwaÃÂ  keduaÃÂ sampelÃÂ berdistribusiÃÂ normal.ÃÂ DataÃÂ diujiÃÂ normalitas,ÃÂ homogenitasÃÂ danÃÂ ujiÃÂ tÃÂ (ujiÃÂ hipotesis).ÃÂ HasilÃÂ analisisÃÂ statistikÃÂ menunjukkanÃÂ adanyaÃÂ perbedaanÃÂ signifikan.ÃÂ RataÃ¢â¬ÂrataÃÂ prestasiÃÂ siswaÃÂ tingkatÃÂ XIÃÂ TMO2ÃÂ sebesarÃÂ 78,81ÃÂ danÃÂ lebihÃÂ ting daripadaÃÂ siswaÃÂ tingÃ¢â¬ÂkatÃÂ XIÃÂ TMO1ÃÂ denganÃÂ rataÃ¢â¬ÂrataÃÂ 74,83.ÃÂ  KataÃÂ kunci:ÃÂ wiringÃÂ diagram,ÃÂ meja,ÃÂ sistemÃÂ pemanasanÃÂ awalÃÂ ÃÂ TheÃÂ aimÃÂ ofÃÂ thisÃÂ researchÃÂ isÃÂ toÃÂ findÃÂ outÃÂ theÃÂ differenceÃÂ betweenÃÂ maintenanceÃÂ andÃÂ ÃÂ repairÃÂ competenceÃÂ ofÃÂ dieselÃÂ engineÃÂ fuelÃÂ systemÃÂ inÃÂ eleventhÃÂ gradersÃÂ atÃÂ SMKÃÂ IslamÃÂ PemalangÃÂ trainingÃÂ yearÃÂ 2008/2009ÃÂ usingÃÂ twoÃÂ differentÃÂ learningÃÂ mediums.ÃÂ  TheyÃÂ  areÃÂ  tableÃÂ  andÃÂ wiringÃÂ  diagramÃÂ  ofÃÂ preheatingÃÂ system.ÃÂ TheÃÂ populationÃÂ andÃÂ sampleÃÂ ofÃÂ theÃÂ reserachÃÂ wereÃÂ eleventhÃÂ gradersÃÂ ofÃÂ TMOÃÂ 1ÃÂ andÃÂ TMOÃÂ 2ÃÂ trainingÃÂ yearÃÂ 2008/2009.ÃÂ DataÃÂ wasÃÂ takenÃÂ fromÃÂ studentÃ¢â¬â¢ÃÂ firstÃÂ abilityÃÂ  toÃÂ  identifyÃÂ  thatÃÂ  bothÃÂ  samplesÃÂ  hadÃÂ  normalÃÂ  distributions.ÃÂ  TheÃÂ  dataÃÂ wasÃÂ  thenÃÂ  testedÃÂ  inÃÂ  accordanceÃÂ withÃÂ  itsÃÂ normality,ÃÂ homogeneity,ÃÂ andÃÂ tÃ¢â¬ÂtestÃÂ (hypothesisÃÂ test).ÃÂ TheÃÂ statisticalÃÂ analysisÃÂ resultÃÂ indicatesÃÂ thatÃÂ thereÃÂ isÃÂ significantÃÂ difference.ÃÂ TheÃÂ averageÃÂ studentsÃ¢â¬â¢ÃÂ achievementÃÂ ofÃÂ eleventhÃÂ gradersÃÂ ofÃÂ TMOÃÂ 2ÃÂ isÃÂ 78,81ÃÂ andÃÂ itÃÂ isÃÂ higherÃÂ thanÃÂ eleventhÃÂ gradersÃÂ ofÃÂ TMOÃÂ 1ÃÂ withÃÂ theÃÂ averageÃÂ 74,83. ÃÂ  Keywords:ÃÂ wiringÃÂ diagram,ÃÂ table,ÃÂ preheatingÃÂ system